2010
DOI: 10.1248/bpb.33.95
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Selective Competitive Binding of Basic Drugs to .ALPHA.1-Acid Glycoprotein Variants

Abstract: The binding of drugs to proteins is an important determinant of their efficacy and/or side-effects in clinical use. Many basic drugs bind mainly to a 1 -acid glycoprotein (AGP), an acute phase reactant, in plasma, but the plasma level of AGP varies greatly in various diseases. It is increased by inflammatory reaction, injury, and surgery, [1][2][3] but decreased by liver cancer, hepatitis and nephritic syndrome. [4][5][6] We have shown that there is a good correlation between the unbound fraction (f u ) of rop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…The imidazole free fractions were found to contain the F1*S variant(s), whereas the A variant eluted later during the imidazole gradient. The fractions were desalted by ultrafiltration, and purity was accessed by isoelectric focusing as previously described (Eap and Baumann, ; Ishizaki et al ., ).…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…The imidazole free fractions were found to contain the F1*S variant(s), whereas the A variant eluted later during the imidazole gradient. The fractions were desalted by ultrafiltration, and purity was accessed by isoelectric focusing as previously described (Eap and Baumann, ; Ishizaki et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…The fractions were desalted by ultrafiltration, and purity was accessed by isoelectric focusing as previously described (Eap and Baumann, 1988;Ishizaki et al, 2010).…”
Section: Separation Of the A And F1*s Variants Of Agpmentioning
confidence: 99%
See 1 more Smart Citation
“…[30,31] Concerning the binding of various basic drugs to the F(1)S and A genetic variants of alpha(1)-acid glycoprotein, it was found that , the higher the affinity of basic drugs for AGP, the more they inhibit the binding of other basic drugs, and further, the inhibitory potency depends on the selectivity of binding to the AGP variants. [32] During specific circular dichroism (CD) probes, dicumarol and acridine orange were found to specifically bind to the F1-S and A variants, respectively. Dicumarol binding to the F1-S variant produced induced Cotton effects originating from the favored chiral conformation of the bound label.…”
Section: Drug Binding Of the Two Main Genetic Agp Variantsmentioning
confidence: 99%
“…The genetic variant composition of individuals, however, shows large variability [9]. The F1*S and A genetic variants were found to have different ligand binding characteristics [10][11][12][13][14]. The exact tertiary structure of AGP has been reported only recently, determining the X-ray structures of the recombinant unglycosylated F1 [15] and A [16] variants.…”
Section: Introductionmentioning
confidence: 99%